ANALISIS INDEKS PEMBANGUNAN KETENAGAKERJAAN DI PROVINSI JAWA TENGAH - Madya Tantri Hapsari; Gentur Jalunggono (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2021)
This study has several objectives, one of which is to analyze the results of the Employment Development Index in the area of Central Java Province. It also wants to provide an overview of the current labor conditions in Central Java as a reference for the determination of policies that will be applied next time. The method used in this research process is a descriptive qualitative analysis method, namely by analyzing the workforce based on the main employment and status of the main job; level of education; level of productivity; etc. Based on the results of the research, the proposed program plan is about increasing the welfare of the community which will ultimately be in line with the increase in the Employment Development Index.